"My Body. My Choice": A Qualitative Study of the Influence of Trust and Locus of Control on Postpartum Contraceptive Choice. Issue 2 (1st February 2018) - Sundstrom, Beth; Szabo, Caitlin; Dempsey, Angela
Abstract : Postpartum contraception helps reduce unintended pregnancy and space births to improve maternal and child health. This study explored women's perceptions of contraceptive choice during the postpartum period in the context of locus of control and trust in healthcare providers. Researchers conducted six focus groups with 47 women, ages 18–39, receiving postpartum care at an outpatient clinic. Techniques from grounded theory methodology provided an inductive approach to analysis. HyperRESEARCH 3.5.2 qualitative data analysis software facilitated a constant-comparative coding process to identify emergent themes. Participants expressed a preference for relationship-centered care, in which healthcare providers listened, individualized their approach to care through rapport-building, and engaged women in shared decision-making about contraceptive use through open communication, reciprocity, and mutual influence. Conflicting health messages served as barriers to uptake of effective contraception. While participants trusted their healthcare provider's advice, many women prioritized personal experience and autonomy in decisions about contraception. Providers can promote trust and relationship-centered care to optimize contraceptive uptake by listening, exploring patient beliefs and preferences about contraception and birth spacing, and tailoring their advice to individuals. Results suggest that antenatal contraceptive counseling should incorporate information about effectiveness, dispel misconceptions, and engage patients in shared decision-making.